HUBUNGAN ANTARA POLA ASUH DENGAN REGULASI EMOSI PADA REMAJA AKHIR YANG DIBESARKAN OLEH SINGLE PARENT - Muhammad Rivaldy; Untung Subroto (STKIP Subang, 2026)
This study aims to examine the relationship between parenting and emotional regulation in adolescents raised by single parents in Jakarta. The study used a correlational design, and involved 206 late adolescent participants aged 18-21 who were raised by single parents. Data were collected using Parental Authority Questionnaire (PAQ) and Emotion Regulation Questionnaire (ERQ) instruments, and then analyzed using inferential statistics. The results showed a strong and significant positive relationship between parenting and emotional regulation in adolescents raised by single parents (rho = 0.640; p < 0.001). These findings indicate that the more positive the quality of care provided by single parents, the better the ability of adolescents to regulate their emotions.